(n, m) Assignments and quantification for single-walled carbon nanotubes on SiO2/Si substrates by resonant Raman spectroscopy1. Issue 24 (28th June 2015) - Zhang, Daqi; Yang, Juan; Yang, Feng; Li, Ruoming; Li, Meihui; Ji, Dong; Li, Yan
<x xml:space="preserve">Abstract</x> An ωRBM–dt relation specifically suitable for random SWNTs on SiO2/Si substrates grown by various catalysts.